COVID-19, Green Innovation and Their Impacts on Financial Performance - Ramadhan, Prasetyo; Iranti, Riri; Dohan, Dohan; Purnama, Yuanita; Riduan Nazir, Weilly (E-Jurnal Akuntansi; Vol 32 No 12 (2022), 2022)
In the face of pandemics like COVID-19 today, environmental issues such as green innovation become very important, because companies with high levels of social and environmental awareness indicate that the companies are more resilient. This study aims to analyze the impact of COVID-19 and green innovation on financial performance. This study uses the Vector Error Correction Model (VECM) as a data analysis method and uses purposive sampling to get 48 samples with 336 observations. The results of this study indicate that COVID-19 has a significant negative impact on financial performance in the long and short term, managers ought to take note of the converting surroundings outside and adjust their commercial enterprise strategies in time. Meanwhile green innovation has a positive impact on financial performance in the long and short term. The implementation of green innovation activities affected the competitiveness and ?rm pro?ts. Keywords: COVID-19; Green Innovation; Financial Performance; VECM